Paul, scripture and ethics : a study of 1 Corinthians 5-7 - Rosner, Brian S. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1994)
Paul, Scripture and Ethics evaluates the widely held view that Scripture did not play an important role in the formation of Paul's ethics by investigating 1 Corinthians 5-7. It concludes that in spite of the relatively few quotations of Scripture and other indications to the contrary, Scripture is nevertheless a crucial and formative source for Paul's moral teaching. The major lines and many of the details of Paul's ethics in these chapters are traced back into the Scriptures, in most cases by way of Jewish sources. The conclusion is drawn that the Scriptures were for Paul not only "witness to the Gospel" but "written for our instruction". The work has considerable implications for the study of Christian origins, the interpretation of the New Testament and for the question of Paul and the Law.